Hukum Adat Dari Tradisi Perkawinan (Uang Japuik Dan Uang Hilang) Yang Berasal Dari Daerah Padang Pariaman Sumatera Barat - Nadia Asmelinda; Erlina B; Okta Ainita (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Indonesia has a reflection or picture of the personality of the nation which is commonly referred to as “Customary Law” which is the embodiment of the soul of a nation from one century to another. The law regarding customary law has been contained in Article 18B paragraph (2). Customary marriage is one of several sections of customary law that is still implemented in several regions to this day. Traditional marriages are carried out in the same way as other customary rules, namely following the procedures and rules of the previous ancestors. Traditional marriages are carried out depending on the customs and culture created in the area. Even though it is not the same as the procedures for traditional marriages and traditions from other regions, traditional marriages do not affect how the beliefs or religions are believed by each person who undergoes them. In modern life like today, there are still many who use the customs of their ancestors which are used as a condition for a marriage. One of the traditional marriages that is currently still being carried out by couples from the city of Pariaman, West Sumatra is the Bajapuik and Uang Hilang. Abstrak: Indonesia memiliki sebuah pencerminan atau gambaran dari kepribadian bangsa yang biasa disebut dengan “Hukum Adat” yang adalah penerapan dari jiwa suatu negara tersebut dari suatu zaman ke zaman. Undang-Undang mengenai hukum adat telah tertuang dalam Pasal 18B ayat (2). Perkawinan adat adalah suatu bagian hukum adat yang masih terlaksana di beberapa daerah sampai saat ini. Perkawinan adat dilaksanakan sama dengan aturan adat lain, yaitu mengikuti tata cara dan aturan nenek moyang terdahulu. Perkawinan adat dilakukan tergantung dengan adat dan budaya yang tercipta pada daerah tersebut. Walaupun tidak sama seperti tata cara dari perkawinan adat dan tradisi dari daerah lain, perkawinan adat tidak mempengaruhi bagaimana kepercayaan atau agama yang dipercayai masing-masing orang yang menjalaninya. Dalam kehidupan yang modern seperti saat ini, masih banyak yang menggunakan adat istiadat dari nenek moyang yang dijadikan syarat adanya sebuah pernikahan. Salah satu perkawinan adat yang saat ini masih banyak dilakukan oleh pasangan yang berasal dari kota Pariaman, Sumatera Barat adalah adat Bajapuik dan Uang Hilang